2001
DOI: 10.1038/35074138
|View full text |Cite
|
Sign up to set email alerts
|

CONSTANS mediates between the circadian clock and the control of flowering in Arabidopsis

Abstract: Flowering is often triggered by exposing plants to appropriate day lengths. This response requires an endogenous timer called the circadian clock to measure the duration of the day or night. This timer also controls daily rhythms in gene expression and behavioural patterns such as leaf movements. Several Arabidopsis mutations affect both circadian processes and flowering time; but how the effect of these mutations on the circadian clock is related to their influence on flowering remains unknown. Here we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
925
3
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,278 publications
(965 citation statements)
references
References 29 publications
31
925
3
6
Order By: Relevance
“…22, 37 and 40). In contrast, the cry2 mutant has also been found to flower at about the same time as the wild type when grown in light rich in FR (12,37). One explanation for this discrepancy is that the cry2 action depends on the presumed active form of phytochrome (Pfr) that decreases in plants grown in light rich in FR (37).…”
Section: Three Photoreceptor Pathways Regulate Flowering Time In Arabmentioning
confidence: 98%
See 1 more Smart Citation
“…22, 37 and 40). In contrast, the cry2 mutant has also been found to flower at about the same time as the wild type when grown in light rich in FR (12,37). One explanation for this discrepancy is that the cry2 action depends on the presumed active form of phytochrome (Pfr) that decreases in plants grown in light rich in FR (37).…”
Section: Three Photoreceptor Pathways Regulate Flowering Time In Arabmentioning
confidence: 98%
“…According to this hypothesis, the light signal must interact at the appropriate time of the day (or ''coincide'') with the photoperiodic response rhythm (PRR) of a cellular activity to confer photoperiodic responsiveness. It has been found that mRNA expression of flowering-time genes in Arabidopsis, including CO, GI, and FT, exhibited circadian rhythms, which have different phase shapes in plants grown in LD compared with plants grown in SD (9)(10)(11)(12). Therefore, the day-length-dependent circadian expression of one or more flowering-time genes may represent the PRR.…”
mentioning
confidence: 99%
“…This is achieved through control of its transcription by the circadian clock and regulation of CO protein stability by light exposure (Andres & Coupland, 2012; Song et al , 2014). Accumulation of CO transcripts therefore forms a diurnal rhythm for timekeeping under LDs and SDs (Suarez‐Lopez et al , 2001). Under LDs CO transcription is controlled by a clock‐controlled blue light photoreceptor FLAVIN‐BINDING, KELCH REPEAT, F‐BOX1 (FKF1), clock‐controlled CYCLING DOF FACTOR (CDFs) transcription factors, and a clock protein GIGANTEA (GI).…”
Section: Introductionmentioning
confidence: 99%
“…By reverse genetics, we have identified candidate genes to regulators of shade-avoidance responses; ATHB2 orthologs (Ciarbelli et al 2008), photomorphogenesis and seedling establishment; FHY3/FAR1, NDPK2, PIF/PIL family, PP7, RAP1/ ATMYC2, RFI2 (Shen et al 2005;Yadav et al 2005;Chen and Ni 2006;Lin et al 2007;Genoud et al 2008;Leivar et al 2008), light-regulated proteolysis; COP1, EID1, LAF1, SPA1 (Yi and Deng 2005;Marrocco et al 2006;Yang et al 2009;Chen et al 2010;Fankhauser and Ulm 2011) and developmental transitions; CO, PFT1 (Suárez-López et al 2001;Cerdán and Chory 2003) (Table S2). Using the obtained sequence information in a reverse genetics approach, we have identified a novel petunia mutant carrying a mutation in CCT (CO, CO-like, TOC1) domain (Strayer et al 2000;Valverde 2011).…”
Section: Discussionmentioning
confidence: 99%